Modern Inventory Control Techniques and Supply Chain Performance of Major Retail Stores in Kisii Town - Seme, Sophy Naeku; Moturi, Damaris (International Journal of Supply Chain and Logistics, 2025)
Purpose: The aim of this study was to find out the influence of modern inventory control techniques on supply chain performance of retail stores in Kisii Town. Methodology: The study adopted a cross sectional study design. The unit of analysis for this study was 83 stores managers of the retail stores. Purposive sampling was be used to select the samples for the study. The study made use of questionnaires to collect primary data. A pilot test was conducted to test the reliability and validity of the data collection instruments. SPSS software program was used to facilitate data processing and analysis. Descriptive and inferential statistics were used to analyze quantitative data. Findings: The findings indicated that economic order quantity inventory control technique, re-order point, fixed stock levels and FSN analysis techniques positively influenced supply chain performance of retail stores in Kisii Town. Unique Contribution to Theory Practice and Policy: The study recommended that management of retail stores should use the inventory control techniques to only store what was being required in the production process but to enhance the overall store performance.